Simulation and Statistics with Excel : Introduction to business students - Ibarra, Luis Fernando (Boca Raton : CRC Press, 2024)
The use of simulation techniques has increased in importance in recent history, and simulation activities are an important resource for advanced preparation for the organization and execution of events. When formal mathematics is not enough, simulation may be the only option capable of approximating solutions. Simulation and Statistics with Excel: An Introduction to Business Students offers a non-rigorous and practical tour of the simulation procedure on computers, using a versatile and accessible resource, the Microsoft Excel spreadsheet. This book covers the concepts essential to understanding the basic principles and approaches of statistical simulation, allowing for the study of complex systems. Aimed at students in business and operational research beginning to use simulation as an instrument for understanding existing or proposed processes, this book will lay solid foundations in understanding simulation experimentation.
Includes bibliography and index.
Keywords: Microsoft Excel; Simulation methods; Uncertainty and Random Numbers; Introduction to Excel; Formulation of Basic Simulations